E-Learners’ Self-efficacy for Online Courses: Self-efficacy for IT Use as a Predictor for Academic Self-efficacy: Saleha Ali (PJDOL, 2023)
The purpose of current study was to investigate the level of students’ self-efficacy, specifically the use of Information Communication Technologies and performing academic tasks for online courses. A quantitative descriptive survey was conducted to explore the problem. The participants were selected from two departments (Arts and Computer Science) of a university. All the students from the Department of Arts were included in study sample and non-proportional random sampling technique was used for selecting participants from the department of CS. In this way, self-tailored five-point Likert Scale was distributed to 603 sampled participants. The study concluded that elearners’ had moderate level of self-efficacy to perform academic tasks and their level of self-efficacy to use ICT was at higher level. There was highly significant positive relationship between academic self-efficacy and self-efficacy to use ICT.The study found that the self-efficacy for IT use is a good predictor of academic self-efficacy.